2012
DOI: 10.14569/ijacsa.2012.030931
|View full text |Cite
|
Sign up to set email alerts
|

The Impact on Effectiveness and User Satisfaction of Menu Positioning on Web Pages

Abstract: Abstract-The authors of this paper are conducting research into the usability of menu positioning on web pages. Other researchers have also done work in this area, but the results are not conclusive and therefore more work still needs to be done in this area. The design and results of an empirical experiment, investigating the usability of menu positioning on a supermarket web site, are presented in this paper. As a comparison, the authors tested a left vertical menu and a fisheye menu placed horizontally at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…On the other hand, the placement of tab menus on the top can facilitate menu navigation to some extent. According to previous studies on websites, it was reported that the top and left placed menus can elicit higher correctness rate, fewer mouse clicks and higher preferences among users (Murano and Oenga 2012;Burrell and Sodan 2006).…”
Section: Designing For Menu-oriented Navigationmentioning
confidence: 98%
“…On the other hand, the placement of tab menus on the top can facilitate menu navigation to some extent. According to previous studies on websites, it was reported that the top and left placed menus can elicit higher correctness rate, fewer mouse clicks and higher preferences among users (Murano and Oenga 2012;Burrell and Sodan 2006).…”
Section: Designing For Menu-oriented Navigationmentioning
confidence: 98%
“…Navigating a Web site efficiently and pleasurably is an important aspect that all Web designers and businesses should be concerned about. Some research has been carried out on Web navigation and menu structures (e.g., Murano and Sander, 2016;Murano and Khan, 2015;Murano and Lomas, 2015;Murano and Oenga, 2012). However, another aspect of navigation that requires more attention is navigating within a Web page by means of scrolling.…”
Section: Introductionmentioning
confidence: 99%